2020
DOI: 10.1101/2020.04.26.20079988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methods of An Open-Label Proof-Of-Concept Trial of Intravenous Valproic Acid for Severe COVID-19

Abstract: word count: 254 Text word count: 1680

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The reported side effects like hepatotoxicity and teratogenicity are mainly associated with the parental compound valproate and can be avoided by the use of its derivatives like Valpromide (VPD) and valnoctamide (VCD). A recent open-label proof-of-concept trial of 10 days Intravenous Valproic Acid for Severe COVID-19 showed a 50% reduction in the case fatality rate and length of stay (38). More studies are needed to explore the promising potential of valproic acid in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The reported side effects like hepatotoxicity and teratogenicity are mainly associated with the parental compound valproate and can be avoided by the use of its derivatives like Valpromide (VPD) and valnoctamide (VCD). A recent open-label proof-of-concept trial of 10 days Intravenous Valproic Acid for Severe COVID-19 showed a 50% reduction in the case fatality rate and length of stay (38). More studies are needed to explore the promising potential of valproic acid in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that glutathione may also interact with viral proteins. Valproic acid is a short chain fatty acid with antiviral activity against several viruses ( 42 , 43 ) and might also be effective against SARS-CoV-2 ( 44 , 45 , 46 ). Therefore, the network- and sequence similarity-based methods identified compounds that may limit viral activities.…”
Section: Discussionmentioning
confidence: 99%